Green Synthesis of Silver Oxide Nanoparticles for Photocatalytic Environmental Remediation and Biomedical Applications - Mir Sayed Shah Danish; Liezel L. Estrella-Pajulas; Ivy Michelle Alemaida; Maria Luisa Grilli; Alexey Mikhaylov; Tomonobu Senjyu (Metals, 2022)
Among the most notable nanotechnology applications is its employment in environmental remediation and biomedical applications. Nonetheless, there is a need for cleaner and sustainable methods in preparing nanomaterials that use cheaper, more environment-friendly precursors than the conventional synthesis process. The green chemistry approach for the preparation of nanoparticles is becoming more attractive as it uses non-toxic chemicals and reagents. It also offers cost-effective synthesis process as it uses readily available plant sources and microbe as redox mediators in converting metallic cations to metal or metal oxide nanoparticles. The extracts of these plants and microbe sources contain phytochemicals and metabolites in variable quantities, which serve as redox mediators and capping agents that stabilize the biosynthesized nanoparticles. The present article reviews the recent studies on the fabrication of silver oxide nanoparticles (Ag2O-NPs) via plant-mediated and microbe-mediated green synthesis, giving a concise discussion on the green preparation of Ag2O-NPs employing extracts of different plants and microbial sources. The performances of the biosynthesized Ag2O-NPs are also reviewed, highlighting their potential use in photocatalysis and biomedical applications.